Differential item and test functioning of the Brief Child and Family Phone Interview in First Nations and non-First Nations children and adolescents / by Dana Bova. - Bova, Dana Louise (2006)
In 2001 the Ontario Ministry of Social Services mandated that all Ontario funded providers of children mental health services utilize the BCFPI (Brief Child and Family Phone Interview) which assesses emotional and behavioural disorders in children and adolescents. It evaluates : regulation of attention impulsivity activity level cooperation with others conduct separation from parents managing anxiety managing mood, and in addition, it explores how these problems influence the child's academic, social and family functioning.--Leaf 21